Coordinated action, communication, and creativity in basketball in superdiversity. (2nd January 2018) - Callaghan, John; Moore, Emilee; Simpson, James
ABSTRACT: This paper examines the complex social space of basketball training sessions at a sports centre in superdiverse inner-city Leeds, contextualising the site in relation to stigmatising discourses that suggest disorderliness and a lack of social cohesion. The microanalysis of video data from the training sessions counteracts these discourses by showing how social orderliness, cooperation, and creativity unfold in the details of interaction. The significance of its contribution lies in its analysis of communication that bridges across semiotic modes, extending the concept of translanguaging to encompass embodied practice. This practice contributes to constituting a small culture within the basketball club.